Recolonizing gray wolves increase parasite infection risk in their prey. Issue 4 (22nd January 2018) - Lesniak, Ines; Heckmann, Ilja; Franz, Mathias; Greenwood, Alex D.; Heitlinger, Emanuel; Hofer, Heribert; Krone, Oliver
Abstract: The recent recolonization of Central Europe by the European gray wolf ( Canis lupus ) provides an opportunity to study the dynamics of parasite transmission for cases when a definitive host returns after a phase of local extinction. We investigated whether a newly established wolf population increased the prevalence of those parasites in ungulate intermediate hosts representing wolf prey, whether some parasite species are particularly well adapted to wolves, and the potential basis for such adaptations. We recorded Sarcocystis species richness in wolves and Sarcocystis prevalence in ungulates harvested in study sites with and without permanent wolf presence in Germany using microscopy and DNA metabarcoding. Sarcocystis prevalence in red deer ( Cervus elaphus ) was significantly higher in wolf areas (79.7%) than in control areas (26.3%) but not in roe deer ( Capreolus capreolus ) (97.2% vs. 90.4%) or wild boar ( Sus scrofa ) (82.8% vs. 64.9%). Of 11 Sarcocystis species, Sarcocystis taeniata and Sarcocystis grueneri occurred more often in wolves than expected from the Sarcocystis infection patterns of ungulate prey. Both Sarcocystis species showed a higher increase in prevalence in ungulates in wolf areas than other Sarcocystis species, suggesting that they are particularly well adapted to wolves, and are examples of "wolf specialists". Sarcocystis species richness in wolves was significantly higher in pups than in adults. "Wolf specialists" persisted during wolf maturation. The results of this study demonstrate that (1) predator–prey interactions influence parasite prevalence, if both predator and prey are part of the parasite life cycle, (2) mesopredators do not necessarily replace the apex predator in parasite transmission dynamics for particular parasites of which the apex predator is the definitive host, even if meso‐ and apex predators were from the same taxonomic family (here: Canidae, e.g., red foxes Vulpes vulpes ), and (3) age‐dependent immune maturation contributes to the control of protozoan infection in wolves. Abstract : The recolonization of Central Europe by the gray wolf ( Canis lupus ) allows for the study of parasite transmission dynamics of the protozoan Sarcocystis, which uses wolves as definitive host and their prey as intermediate hosts, respectively. Our study indicates that wolves have returned as the apex predator of red deer ( Cervus elaphus ), resurrecting red deer‐specific parasite life cycles as red deer, in contrast to roe deer and wild boar, are affected by a significant increase in parasite prevalence when wolves are present in their habitat. Furthermore, the two parasite species Sarcocystis grueneri and Sarcocystis taeniata appear to be well adapted to wolves as (1) they occur more often in wolves than expected from their presence in wolf prey and (2) because they persist during wolf maturation while other parasite species fade.